KARAKTERISTIK PATI PISANG KEPOK (Musa paradisiaca var. formatipyca) TERMODIFIKASI DENGAN METODE IKATAN SILANG MENGGUNAKAN SODIUM TRIPOLYPHOSPHAT (STPP) - Armayuni, Putu Hetty; Timur Ina, Putu; Wiadnyani, AA Istri Sri (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 5 No 1 (2016): Jurnal ITEPA, 2016)
Research aims is to find the effects of sodium tripolyphosphat (STPP) concentration on the characteristic of modified kepok banana starch and to determine the optimal concentration of  STPP that can produced the best characteristic of modified kepok banana starch. This study was an experimental study designed by Randomized Block Design (RBD), with the treatment given is the difference in 5 levels concentration of STPP which consist such as 0%, 1%, 3%, 5% and 7%. The whole treatment was repeated three times to obtain 15 experiment units. Data were analyzed by analysis of variance and if there was a treatment effects on observed then followed by Duncan multiple range test. The results showed that concentration of STPP significant effeted the characteristic of modified kepok banana starch. Higher the concentration of STPP added can improve the phosphate content, degree of substitution, amylose content, starch content, and swelling power. The best characteristic properties of modified kepok banana starch was produced by 7% of STPP concentration with a phosphate content of 0.283%, degree of substitution of 0.015, amylose content of 21.349%, starch content of 62.653%, swelling power of 10.374 g/g and solubility  of 0.122%.
Keywords: starch, kepok banana, cross linking, STPP